Does the shape of the electric pulse matter in electroporation? - Novickij, Vitalij; Rembiałkowska, Nina; Szlasa, Wojciech; Kulbacka, Julita (Frontiers in Oncology, 2022)
Electric pulses are widely used in biology, medicine, industry, and food processing. Numerous studies indicate that electroporation (EP) is a pulse-dependent process, and the electric pulse shape and duration strongly determine permeabilization efficacy. EP protocols are precisely planned in terms of the size and charge of the molecules which will be delivered to the cell. In reversible and irreversible EP applications, rectangular or sine, polar or bipolar pulses are commonly used. The usage of pulses of the asymmetric shape is still limited and not clarified. This review highlights the importance and role of the pulse shape and course in their effects on cellular processes and membrane permeabilization.